DEVELOPING ENGLISH READING MATERIALS FOR LIGHT VEHICLE ENGINEERING DEPARTMENT - Imamul Khaira; Anni Holila Pulungan (Universitas Negeri Medan, 2017)
This study is aimed to develop English reading materials for vocational school.This study was conducted by using Research and Development (R&D). Thesubject of this research was Grade X students of Light Vehicle EngineeringDepartment of SMK YPT Pangkalan Brandan consisting of 22 students. The dataconsist of syllabus, lesson plan, syllabus and existing materials. Instrument ofcollecting data were questionnaires and interview which were used to collectinformation about students’ needs and learning needs. The need analysis showedthat 81.8 % of students had difficult to understanding English reading text becausethe text is not relevant, difficult to understand the structure of word and sentencesin reading text and difficult to conclude the reading text. The evaluation ofexisting reading materials showed that the existing reading materials are notintended for students of Light Vehicle Engineering Department. The existingreading materials are intended for all vocational students. After the students’ needand reading materials had been analyzed, the new reading material was developedthat considering the students’ need and the relevant with vehicle. The genre of thereading texts which were developed is descriptive text. Based on basiccompetence, kinds of descriptive text which developed are describing people,tourism place, and historical building. The product of this study consists of fivechapters which titles are Soichiro Honda, Museum Angkut, Coventry TransportMuseum, TMII Transport Museum, and Cadillac Ranch. The product wasvalidated by an English teacher and an English lecturer with the mean score is 4.1from 5. The product is categorized as “Good and Relevant” reading materials.